Finishing properties of polyurethane, nitrocellulose and acid-catalysed based coatings on rengas (gluta sp.) / Judith Gisip - Gisip, Judith (2001)
In this study, the coatings properties and performance were determined by conducting 9 types of tests, which reveal the resistance of the coatings towards mechanical property, abrasion, chemical, heat, adhesion and also the property of gloss. Types of coating studied include Polyurethane, Nitrocellulose, and Acid-Catalysed where they were applied using four different types of finishing system i.e.: A: Wood Filler + Sealer + Top coat, B: Sealer + Top coat, C: Wood Filler + Top coat, and D: Three layers of top coat. PU and AC perform well in all tests. Meanwhile, system D is suitable to be applied when concerning with properties such as abrasion, hardness, scratch and gloss. System C is the best system to resist heat and system B is the best system for adhesion. The combination of PU with system D is best for gloss and hardness properties. When applied with system C, PU provides good abrasion resistance. AC is best applied with system C to resist heat and scratch whereas when combined with system B and D, it is good towards adhesion.